Impact of Vitamin D Deficiency on Iron Deficiency Anemia: A Comparative Analysis in Iraqi Population - Omar, Sleman Y.; Awla, Awat H.; Salih, Musher I.; Hamadamin, Badinan J. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
Two important health problems are iron deficiency anemia and vitamin D deficiency, as well as the ability to cope with acute and chronic diseases, because iron and vitamin D are the main elements of physiological functions in the human body. Recent studies have indicated that generalized IDA in both healthy and diseased populations may be associated with inadequate levels of VD. The research comprised 132 participants, 65 with IDA and 67 controls, the study was conducted in a competent cross-sectional design, between the two groups matched by age and gender. The laboratory findings included the study of blood indices. Ferritin, iron, hemoglobin, mean corpuscular volume, red cell distribution width, and VD levels were measured for each participant. Iron metabolism markers showed highly significant variations between the groups. Patients with IDA exhibited considerably lower levels of iron indicators than the healthy control group, except for total iron binding capacity (TIBC), which was increased among the patients. The normal control group showed substantially higher serum VD levels than patients with iron deficient anemia (p < 0.035). This distinction suggests a high positive link between VD levels and iron metabolism markers, except for TIBC, which exhibited a negative correlation. The results showed a significant correlation between VD levels and several iron metabolism markers in the research participants. This suggests that VD may affect how iron is metabolized and help treat IDA. To fully understand the underlying mechanisms and any therapeutic benefit, further research is needed.